The Effect of Incorporation of Multi-Walled Carbon Nanotube into Poly(Ethylene Oxide) Gel Electrolyte on the Photovoltaic Performance of Dye-Sensitized Solar Cell. Issue 1 (2nd January 2019) - Xianhua, Chan; Khanmirzaei, Mohammad Hassan; Omar, Fatin Saiha; Kasi, Ramesh; T. Subramaniam, Ramesh
ABSTRACT: Gel polymer electrolytes (GPEs) consist of poly(ethylene oxide) (PEO), sodium iodide (NaI) and different amount of multi-walled carbon nanotubes (MWCNT) were prepared. The conductivity study revealed that the highest ionic conductivity of GPE was 7.02 × 10 −3  S cm −1 . The structural and complexation between the materials are authenticated via X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. Under the exposure of AM 1.5, the fabricated DSSCs exhibited the highest photoenergy conversion efficiency of 7.23% with a short circuit current density (JSC ) of 18.64 mA cm −2, open circuit voltage (VOC ) of 0.590 mV and fill factor (FF) of 65.7%. GRAPHICAL ABSTRACT: GRAPHICAL ABSTRACT